AUTONOMOUS CENTRAL SPECIALISED AUTHORITIES - Elena Emilia ȘTEFAN (Challenges of the Knowledge Society)
Within the public administration organisation system, a special place is given to the autonomous specialised central authorities, regulated by the Constitution. Such a constitutional rank authority is the Economic and Social Council. In view of the fact that, according to the Constitution, the Economic and Social Council is an advisory body of Parliament and the Government, without detailing the areas of expertise in which it is consulted, there is a question in what concerns the way in which it fulfils its role established by the legislator. Therefore, the scope of this study is to know the legal regime of this autonomous central specialised authority, according to the legislation and specialised doctrine. Furthermore, the analysis will place the Economic and Social Council in an international context, in the sense that we will research in comparative law what is provided for in the constitutions of other European countries regarding this authority. From this point of view, we consider the topic to be of interest to legal specialists as it provides information about a public authority of constitutional rank. In this respect, by means of law-specific researched methods, such as documentary method, comparative method and logical-deductive method, we will underline the conclusion of our paperwork, that, among other duties, the Economic and Social Council, being involved in the broad legislative process, according to its organic law, issues opinions and carries out an activity in the public interest.